The creative process of creating dance accompaniment gendhing Murdanata Dedarining Aringgit: the mascot dance of Nagasepaha Village in Buleleng Regency, Bali - Kariasa, I Nyoman; Wardizal, Wardizal; Santosa, Hendra (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2023)
The Gendhing accompaniment for Murdanata Dedarining Aringgit is a newly composed musical piece designed to accompany the Murdanata Dedarining Aringgit dance, which serves as the mascot dance of Nagasepaha village in Buleleng Regency, Bali. Data for creating this piece were gathered through literature studies, observations, interviews, and discography (recordings). The primary question guiding this creation was: 'What is the creative process involved in composing the accompaniment for the Murdanata Dedarining Aringgit dance?' The creative process involved three stages: exploration, improvisation, and formation. The key findings of this creation include: (1) The Gendhing accompaniment for Murdanata Dedarining Aringgit is a novel composition rooted in Balinese karawitan musical concepts, (2) The structural framework of the Gendhing utilizes the Tri Angga concept, comprising Kawitan, Pengawak, and Pengecet, and (3) Both the Gendhing and the Murdanata Dedarining Aringgit dance emerged from a collective desire to establish a new musical language that fulfills the community's evolving cultural needs. This creation underscores the inseparable unity between the Gendhing accompaniment and the Murdanata Dedarining Aringgit dance, thus serving as a cultural representation of the people of Nagasepaha village in Buleleng Regency, Bali.